How Markets Work: The Lawyer's Version - Weidemaier, W. Mark C.; Gulati, Mitu (Studies in Law, Politics & Society, 2013)
This article combines two sources of data to shed light on the nature of transactional legal work. The first consists of stories about contracts that circulate among elite transactional lawyers. The stories portray law-yers as ineffective market actors who are uninterested in designing super-ior contracts, who follow rather than lead industry standards, and who depend on governments and other outside actors to spur innovation and correct mistakes. We juxtapose these stories against a dataset of sover-eign bond contracts produced by these same lawyers. While the stories suggest that lawyers do not compete or design innovative contracts, their contracts suggest the contrary. The contracts, in fact, are consistent with a market narrative in which lawyers engage in substantial innovation despite constraints inherent in sovereign debt legal work. Why would lawyers favor stories that paint them in a negative light and deny them a potent role as market actors? We conclude with some conjectures as to why this might be so.
Law
Keywords: POLANYI; Karl; 1886-1964; contracts; international finance; lawyers; lead industry; socioeconomics; sovereign debt; transactional marketing